Um estranho no ninho? a (des)construção identitária do aluno surdo em escolas inclusivas de Feira de Santana - Carneiro, Gustavo Leão de Mello (2023)
This research intends to analyse the cultural manifestations of deaf students at two inclusive schools in Feira de Santana, as well as we intend to identify the factors that both weaken and strengthen those students’ identity constitution. The participants of this study were five hearing people, five deaf students, eight hearing students and the coordination staff from both institutions. To develop this study, the concepts of culture, deaf culture, identity, and deaf identities are the ones which based the discussions we present here. Besides, the discussions about culture and identity are based on the ideas of both Santos (2009) and Hall (2010). Under the same point of view, both Strobel (2008) and Perlin (2002; 2004; 2007; 2014) based the studies about deaf culture and deaf identities. The selected methodological option was the qualitative research and the ethnographic approach. In the meantime, to collect the data, we used semi-structured interviews, a focal group and non-participative observations. The results show us that even though there are factors which can strengthen the deaf culture and the interaction amongst the several actors involved in this study, it is possible to notice a sort of linguistic barrier, due to the lack of the Brazilian Sign Language (LIBRAS) knowledge in the various school groups observed and even in some of the deaf students, leading to the frailty of the deaf culture manifestations and also having an impact on the deaf students’ identity construction.